2023
DOI: 10.3233/jad-220758
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Provides Broad Therapeutic Benefits in an Alzheimer’s Disease Mouse Model

Abstract: Background: Alzheimer’s disease (AD) is a chronic neurodegenerative disorder with a progressive loss of cognitive function. Currently, no effective treatment regimen is available. Lithium, a mood stabilizer for bipolar disorder, exerts broad neuroprotective and neurotrophic actions and improves cognitive function. Objective: The study investigated if lithium stabilizes Ca2+ signaling abnormalities in hippocampal neurons and subsequently normalize downstream effects on AD neuropathology and synaptic plasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…Imatinib and imatinib methanesulfonate could prevent Aβ formation by inhibiting GSAP ( He et al, 2010 ; Weintraub et al, 2013 ; Chu et al, 2014 ). Lithium treatment reduced abnormal IP3R-dependent ER Ca 2+ signaling and enhanced synaptic plasticity in 3 × Tg AD mice ( Wiseman et al, 2023 ). Xestospongin C can ameliorate the Ca 2+ overload of primary hippocampal neurons induced by Aβ 1–42 and improve the cognitive ability of APP/PS1 mice ( Wang et al, 2019 ).…”
Section: Strategies Targeting Mams For Treating Admentioning
confidence: 99%
“…Imatinib and imatinib methanesulfonate could prevent Aβ formation by inhibiting GSAP ( He et al, 2010 ; Weintraub et al, 2013 ; Chu et al, 2014 ). Lithium treatment reduced abnormal IP3R-dependent ER Ca 2+ signaling and enhanced synaptic plasticity in 3 × Tg AD mice ( Wiseman et al, 2023 ). Xestospongin C can ameliorate the Ca 2+ overload of primary hippocampal neurons induced by Aβ 1–42 and improve the cognitive ability of APP/PS1 mice ( Wang et al, 2019 ).…”
Section: Strategies Targeting Mams For Treating Admentioning
confidence: 99%
“…Lithium treatment reduces p-tau and neurofibrillary tangles formation in animal models of tauopathies and AD (157)(158)(159). In addition, lithium treatment stabilized neuronal signaling alterations, including aberrant Ca 2+ signaling, restored neuronal nitric oxide synthase (nNOS) and p-tau levels, and enhanced short-term plasticity in the hippocampus of 3xTg-AD mice (160). Nevertheless, the evidence obtained in clinical trials is mixed.…”
Section: Lithiummentioning
confidence: 99%
“…Most studies using APP transgenic AD mouse models have consistently reported that lithium reduces Aβ aggregation, senile plaques, phosphorylated tau (p-tau) formation, neurofibrillary tangles, and neuronal death and improves learning and working memory [28][29][30][31][32][33][34][35]. Studies using p-tau and p-tau/APP transgenic mouse models have also reported that lithium reduces Aβ aggregation, p-tau formation, and neurofibrillary tangles [9, [35][36][37][38]. These studies have suggested that the therapeutic effects of lithium are likely to be associated with its inhibition of glycogen synthase kinase (GSK) 3β [31-33, 35, 39].…”
Section: Lithium Reduces Neuropathology and Enhances Synaptic Plastic...mentioning
confidence: 99%
“…In addition, future studies should consider nonconventional AD models, such as mice with deficiency of NMDA receptor subunit GluN3A, Table 2. The Effects of 30-day lithium treatment on aberrant Ca 2+ signaling, nNOS expression, tau phosphorylation, and synaptic plasticity in 3xTg-AD mice [38] 3xTg-AD mice Non-Tg mice lithium control lithium control which causes calcium dysregulation and AD-like behavioral phenotypes [92]. Moreover, it would be interesting to study the intricate relationships of cytosolic and ER calcium during pathogenesis of AD through recently developed, red-shifted calcium indicator protein for ER [137].…”
Section: Calcium Hypothesis Of Admentioning
confidence: 99%
See 1 more Smart Citation